VLADINOL F, NEOLIGNAN COMPOUND FROM THE STEM BARK OF Dryobalanops oblongifolia (DIPTEROCARPACEAE) AND ANTIPLASMODIAL ACTIVITY - Indriani, .- (Rasayan Journal, 2021)
Drybalanops oblongifolia known as kayu kapur is a plant member of Dipterocarpaceae family. A neolignan, vladinol F, was successfully isolated from the dissolved fraction in acetone-ether of Dryobalanops oblongifolia stem bark. The chemical structure's determination was done based on an analysis of UV-Vis, NMR, and MS spectra and a comparison with the reference. In vitro test of this compound against Plasmodium falciparum 3D7 showed that IC50 value was 3.51 μg/mL.